Mixed-use 'regeneration' of employment land in the post-industrial city: challenges and realities in London. Issue 10 (2nd October 2016) - Ferm, Jessica; Jones, Edward
ABSTRACT: This article explores the relationships between land-use planning, property and economic development, with a focus on the changing attitudes towards employment land in post-industrial cities. Drawing on case study data from two London local authorities, it finds that planning authorities are moving away from protecting employment land to actively promoting the mixed-use redevelopment of employment sites, even when there are thriving businesses on these sites and a shortage of supply of employment premises and land, relative to demand. We examine the drivers for changing policy including the national and regional policy contexts, housing targets, the influence of austerity measures, rise of Neighbourhood Planning and changing conceptions of regeneration and the role of housing therein. The article highlights the complex task faced by local planners and the tensions involved in simultaneously finding sites for housing, fostering economic development and promoting mixed-use redevelopment in planning policy and decisions. We find that changes in policy are fuelling speculation for housing development on sites occupied by viable businesses, supporting rather than responding to deindustrialization. This is leading to a gap between aspirations for delivering mixed-use environments on hitherto employment sites and realities on the ground.